Law enforcement obstacles to traffic violations through electronic tips (Etle) in Surakarta - Indah Sundari Pratiwi; Asri Agustiwi; Bintara Sura Priambada (The International Journal of Politics and Sociology Research, 2023)
Industrial Revolution 4.0. The factor of technological change known as digitization technology is transitioning from analog to digital technology and delivering information from analog to binary format. The rapid development of technology and information has encouraged the Police of the Republic of Indonesia to develop an information system supported by a network or website-based software that enables the dissemination of information to every member of the police in real-time. Electronic Traffic Law Enforcement (ETLE) is a sophisticated camera system that can detect traffic violations on the highway. This research aims to discover the obstacles in Enforcing Traffic Violations through Electronic Traffic Law Enforcement (ETLE). To determine the Effectiveness of Law Enforcement Related to Pass Traffic Violations through Electronic Traffic Law Enforcement (ETLE) or Electronic Tickets. The method used in this study uses a qualitative approach. The qualitative method is a method that focuses on in-depth observation by producing a more comprehensive analysis of a phenomenon. Applying ETLE fines and manual ticketing by the police, in this case, Satlantas, is a form of effort to reduce violations. The data obtained in 2022 shows that violations are increasing. This is because the existence of ETLE tickets can be seen for violators. After all, they are recorded with the ETLE camera recorder, and it is also hoped that it will make it easier for violators to resolve the legal problems they face with effective bureaucratic reform and legal certainty regarding fines obtained from fines. By the violator, but this does not rule out the possibility of the traffic police being constrained by something when showing evidence of a ticket to the violator. And other obstacles, both the facilities and infrastructure for the ETLE ticket